CD7 Expression in Malignant Pleural Mesothelioma - Hibi, Shigeyoshi (Jpn J Cancer Res, 1992)
CD7 antigen was found to be expressed on malignant mesothelioma arising from the right pleura in a 15‐year‐old girl not only by immunostaining using monoclonal antibodies, but also by Northern blot analysis. The level of expression in this tumor was comparable to those in T‐cell lines, Jurkat and CCRF‐CEM. Cytogenetic analysis of the tumor showed hypodiploidy (n = 43). CD7 has been regarded as one of the hematopoietic cell markers selectively expressed on the majority of T cells and multipotential stem cells. To our knowledge, this is the first report of a non‐hematopoietic tumor expressing CD7.